Secretion of Plasminogen Activators by Cultured Bovine Endothelial Cells: Partial Purification, Characterization and Evidence for Multiple Forms - Laug, W E (Thrombosis and Haemostasis, 1981)
Endothelial cells were obtained from the aortae of newborn calves and cloned. High plasminogen activator (PA) activity was detected in the supernatant medium and the cell lysates of confluent cultures. The PA activity in the growth medium increased steadily during 12 hrs of incubation, indicating active enzyme secretion by these cells. Sodium dodecyl sulphate (SDS) polyacrylamide gel electrophoresis of the concentrated medium demonstrated the presence of four plasminogen activators with apparent molecular weights of 77,000 (±3000), 43,000 (±2000), 26,000 (±1500) and 14,500 (±1500) respectively. The 43,000, 26,000 and 14,500 molecular weight forms could be converted to radioactive derivates by active site labeling with 3H diisopropyl fluorophosphate (3H DFP) while the 77,000 Dalton form took up only traces of this radioactively labeled compound. The 43,000 molecular weight form was partially purified by means of salt precipitation and gel filtration. This enzyme preparation activated plasminogen by proteolytic cleavage with maximum activity at pH 7.5-8.5 and demonstrated a specific activity of 80,000 CTA (Committee on Thrombolytic Agents) units/mg protein when tested on 125I-fibrin in the presence of plasminogen. This PA was rapidly and irreversibly inhibited by diisopropyl fluorophosphate (DFP), suggesting that it was a serine protease. The partially purified enzyme was extremely labile at temperatures from 0-60° C, but could be stabilized by lowering the pH to 3 or by the addition of albumin.
Keywords: Endothelial cells; Plasminogen activators; Purification; Characterization